Postoperative residual vertical deviation affects quality of life in Asian patients with thyroid-associated ophthalmopathy (Graves ophthalmopathy) - Chen, Ying-Yi; Wei, Yi-Hsuan; Liao, Shu-Lang (Japanese journal of ophthalmology, 2023)
Purpose To evaluate the treatment effect of strabismus surgery for Graves ophthalmopathy in an ethnic Chinese population. Study design A prospective clinical study. Methods Thirty-one patients with Graves ophthalmopathy who had undergone strabismus surgery at National Taiwan University Hospital between 2012 and 2013 were consecutively recruited. The subjective outcome was evaluated using the Graves’ Ophthalmopathy Quality-of-Life (GO-QoL) questionnaire, and the ocular deviation was measured preoperatively and postoperatively by use of a prism cover test. Results The GO-QoL scores for visual functioning and appearance improved significantly after surgery (preoperative scores 32.6 ± 19.9 and 43.8 ± 26.4, postoperative scores 55.2 ± 24.4 and 54.1 ± 27.6, respectively; P < .05). Motor success was achieved in 61.3% of the patients, and their postoperative visual scores were higher (61.5 ± 22.5) than the scores of those who experienced motor failure (45.3 ± 26.8, P = .048). The postoperative visual function scores showed a negative correlation with the residual vertical deviation ( R 2 = 0.546, P = .040). A higher increase in GO-QoL visual scores and a lower residual vertical deviation in downgaze were achieved among patients without previous decompression surgery. Our surgical methods resulted in a motor success rate of 76.5% for the correction of vertical deviation. Conclusion GO-QoL scores and ocular deviation improved significantly after strabismus surgery. Precise correction of vertical deviation was of greater importance than horizontal deviation for visual function scores. Our surgical methods were effective for the correction of vertical deviation in Graves ophthalmopathy.